Building resilience through climate risk insurance: Insights from agricultural research for development - Kramer, Berber; Hellin, Jonathan; Hansen, James; Rose, Alison; Braun, Mélody (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
Scaling insurance to transfer climate risk from the rural poor to financial markets is vital to enhance agricultural risk management in developing countries, but insurance programs need to address several challenges in order to improve resilience at scale. A mix of stakeholder expertise is required to design, evaluate and scale insurance programs with the potential to enhance resilience among the rural poor. We highlight the contribution that agricultural research for development can play by providing data, methods, impact evaluations and other research products that can help strengthen and verify the impacts of insurance on resilience at scale. These outputs are made available to the insurance industry as public goods in order to overcome challenges around, among others, data availability, targeting and design of insurance, distribution channels and use of technology, bundling with risk-reducing technologies and practices, enabling environments and smart subsidies, and capturing the full value chain.